The A SYSTEMIC STUDY ON THE HOSPITALITY INDUSTRY'S IDENTIFICATION OF INTANGIBLE CAPITAL - Gaurav Khurana, Jitin Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In most cases, the market value of a company and the book value of a company are not equal. Since the 1970s, there has been a large growth in the difference ascribed to intangible assets that have not been documented or recognised. However, the question of how to value these intangible assets remains unanswered. This study's goal is to solve the industry's lack of awareness of the value of intangible assets. Based on past research in the hotel sector, five intangible asset investments: Research and Development, Training, Advertising, Labour, Pension, and one business model, Franchising, were selected as the valuation structures in this study. Both the casual dining and fast service restaurant industries' value methodologies are contrasted. For the first time, a quantitative technique to value intangible assets in the hotel sector has been developed that incorporates valuation components from prior studies. The findings of this study will assist managers in the hotel sector make strategic decisions, particularly in the areas of research and development, advertising, and staff remuneration.